Spectral Music and Minimalism: Reflections on the Work for Voice and Bells by Llorenç Barber - García Fernández, Isaac Diego (Perspectives of New Music, 2024)
THIS ARTICLE REFLECTS ON THE EXPANSION of spectral thinking towards diverse sound manifestations related to musical minimalism. In different creations of minimalistic style, a deep interest towards the nature of sound and its possibilities for projection in time can be appreciated. As opposed to the traditional conception of a musical piece as a linear narration, many of these proposals face a time dimension that is organic and circular, that reveals a special interest for the processes of auditory perception. The work of Spanish composer, sound artist and performer Llorenç Barber (b. 1948) represents a valuable example of heterodox spectral music of minimalist approach. His creations for diaphonic singing and bells explore the acoustic properties of sound from an empirical and intuitive perspective. This way, the timbre, expanded in broad temporal frameworks, becomes the main element that constructs his sound creation.
Keywords: spectral music; minimalism; voice; bells; Llorenç Barber